Behavioral evaluation during dental care in children ages 0 to 3 years - Cunha, Robson Frederico [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Percinoto, Célio [UNESP]; Melhado, Fabíola Lemos (My University, 2003)
Purpose: Many studies concluded that the behavior of babies complicated dental care because of child immaturity or the difficulty of establishing acceptable communication and comprehension. Methods: The records of 696 babies were randomly selected from the baby clinic of Araçatuba in Brazil. Patient age ranged from 0 to 36 months. They were divided into 6 groups according to age: Group I-0 to 6 months; Group II-7 to 12 months; Group III-13 to 18 months; Group IV-19 to 24 months; Group V-25 to 30 months; Group VI-31 to 36 months. The behavior of the child was evaluated upon entrance in the dental office and during the first 4 clinical appointments with a clinical exam and oral physiotherapy. The baby was classified as collaborator (C) or noncollaborator (NC). Statistical analysis was performed using Pearson's chi-square method (P< .05). Results: The percentage of NC for Groups II, III, IV, and V (66%), was significantly higher than for groups I (30%) and VI (50%). Conclusions: Babies from 0 to 6 months showed a collaborative behavior; babies from 7 to 30 months showed noncollaborative behavior; and babies from 31 to 36 months showed no statistically significant difference between the percentage of C and NC.
Keywords: Behavior management; Child behavior; Infant oral health; Brazil; child; child behavior; controlled study; dental care; dental facility; dentistry; evaluation; human; infant; major clinical study; maturity; physiotherapy; randomization; statistical analysis; age; attitude to health; chi square distribution; cooperation; crying; doctor patient relation; mouth hygiene; newborn; physical examination; preschool child; psychological aspect; Age Factors; Attitude to Health; Chi-Square Distribution; Child Behavior; Child, Preschool; Cooperative Behavior; Crying; Dental Care; Dentist-Patient Relations; Humans; Infant; Infant Behavior; Infant, Newborn; Oral Hygiene; Physical Examination